Public Budget Transparency and Accountability in Preventing Corruption and Inefficiency - Ratna Sari; Muslim Muslim (Advances in Management & Financial Reporting, 2026)
Purpose: This study explores the role of public budget transparency and accountability in preventing corruption and inefficiency. It investigates how governance mechanisms and digital tools, such as e-governance and e-procurement systems, affect public trust in government institutions. Research Method: The study employs a systematic literature review, analyzing secondary data from various sources to examine the effectiveness of transparency and accountability across regions. The research focuses on regional differences between developed and developing countries and identifies critical factors such as institutional strength and citizen participation. Results and Discussion: The findings show that transparency mechanisms, particularly those supported by digital technologies, significantly reduce financial reporting errors and enhance public trust. However, transparency alone is not practical in regions with weak governance structures. Successful implementation requires strong accountability measures and active public involvement. Implications: The study suggests governments should combine digital tools with institutional reforms to ensure adequate public oversight and participation. Public administrators and policymakers must develop governance frameworks that encourage transparency and accountability. Future research should examine the influence of political, cultural, and social factors on the success of transparency initiatives.